A multivariate approach to analyzing functional redundancy of marine periphytic ciliates during the colonization process for bioassessment in coastal ecosystems. Issue 1 (15th April 2017) - Xu, Guangjian; Zhong, Xiaoxiao; Warren, Alan; Xu, Henglong
Abstract: Functional redundancy is a useful tool for determining functional compensation and for reducing "signal to noise" ratios of full-species datasets in community-based monitoring programs. The functional redundancy of marine periphytic ciliate communities during the colonization process in coastal waters of the Yellow Sea, China, was analyzed using a peeling procedure (BVSTEP). Four response units (RUs) with trophic-functional equivalents were identified from the full 77-species dataset. These RUs, which comprised four, seven, six and six species respectively, represented a clear variation in trophic-functional structures across the levels of functional redundancy. RU1 was dominated by bacterivores, RU2 and RU3 first by bacterivores then by algivores, and RU4 first by non-selectives and bacterivores then by algivores. The colonization process and growth curve of each RU were significantly well-fitted to the MacArthur-Wilson and logistic models, respectively. These results suggest that RUs can be used as changeable trophic-functional equivalents for bioassessment in marine ecosystems. Highlights: Four response units (RUs) were identified from a dataset of periphytic ciliates. The RUs represented a clear variation across the levels of functional redundancy. The RUs were well fitted to the MacArthur-Wilson and logistic models, respectively. The RUs might be used as useful changeable trophic-functional equivalents.